Innovative numerical modelling in geomechanics - Sousa, L. Ribeiro e; Vargas Jr.Euripedes; Fernandes, Manuel de Matos; Azevedo, Roberto (CRC Press Taylor & Francis, 2012)
Since the 1990s five books on 'Applications of Computational Mechanics in Geotechnical Engineering' have been published. Innovative Numerical Modelling in Geomechanics is the 6th and final book in this series, and contains papers written by leading experts on computational mechanics. The book treats highly relevant topics in the field of geotechnics, such as environmental geotechnics, open and underground excavations, foundations, embankments and rockfill dams, computational systems and oil geomechanics. Special attention is paid to risk in geotechnical engineering, and to recent developments